การนำกลับทองแดงจากน้ำเสียโรงงานชุบโลหะโดยวิธีสกัดด้วยตัวทำละลาย - สิรินุช วชิรวัชรินทร์ (จุฬาลงกรณ์มหาวิทยาลัย, 2004)
Wastewater from electroplating process was contaminated by heavy metal that the removal of metal from wastewater is very difficult. Therefore research is needed in order to determine the method for recovery the metal. This research investigated the recovery of copper from electroplating wastewater by using solvent extraction, LIX 84-I, and the stripping process by aqueous solution of sulfuric acid in shake flask. The waste aqueous solution contained about 4,500 mg/l of copper. In the solvent extraction process, the optimum initial pH was 1.6, and the wastewater/solvent ratio was 10:3. The percentage extraction of copper was 99.83%. The raffinate remained the copper at a concentration of approximately 7.5 mg/l. In the stripping process, the optimum concentration of sulfuric solution was 10 molar, and the sulfuric solution/extract ratio was 1:2. Copper was recovered at a percentage of 57.8%. The sulfuric solution contained copper at a concentration of approximately 17,383 mg/l, which could be used as a raw material in electroplating process. This solvent could be reused as many as 27 times, and corresponded to the sulfuric solution containing copper at a concentration of approximately 28,749 mg/l. Cost estimation for copper recovery from electroplating wastewater using solvent extraction was evaluated. The result indicated that the total cost of the extractant and the chemicals was 5.25 Baht per liter of wastewater (1.22 Baht per gram of copper)